APPLICATION MODELING AND SIMULATION IN TRAINING AIRCRAFT SPECIALIST (Perner's Contacts, 2015)
This paper describes one example of the creation of new solutions simulator system for aircraft L-410 UVV taking into account the necessary changes in technical and technological solutions simulator system.
Keywords: modeling, flight simulator, training